Vaccinomics: A scoping review. Issue 14 (31st March 2023) - Dudley, Matthew Z.; Gerber, Jennifer E.; Budigan Ni, Haley; Blunt, Madeleine; Holroyd, Taylor A.; Carleton, Bruce C.; Poland, Gregory A.; Salmon, Daniel A.
Highlights: Many genetic associations with vaccine immunogenicity have been identified. Most genetic associations identified with Hepatitis B, MMR, and influenza vaccines. Genetic associations were identified with 6 adverse events following immunization. Vaccinomics is a growing field with great potential but need for investment. Progress in vaccinomics could improve vaccine safety and effectiveness. Abstract: Background: This scoping review summarizes a key aspect of vaccinomics by collating known associations between heterogeneity in human genetics and vaccine immunogenicity and safety. Methods: We searched PubMed for articles in English using terms covering vaccines routinely recommended to the general US population, their effects, and genetics/genomics. Included studies were controlled and demonstrated statistically significant associations with vaccine immunogenicity or safety. Studies of Pandemrix®, an influenza vaccine previously used in Europe, were also included, due to its widely publicized genetically mediated association with narcolepsy. Findings: Of the 2, 300 articles manually screened, 214 were included for data extraction. Six included articles examined genetic influences on vaccine safety; the rest examined vaccine immunogenicity. Hepatitis B vaccine immunogenicity was reported in 92 articles and associated with 277 genetic determinants across 117 genes. Thirty-three articles identified 291 genetic determinants across 118 genes associated with measles vaccine immunogenicity, 22 articles identified 311 genetic determinants across 110 genes associated with rubella vaccine immunogenicity, and 25 articles identified 48 genetic determinants across 34 genes associated with influenza vaccine immunogenicity. Other vaccines had fewer than 10 studies each identifying genetic determinants of their immunogenicity. Genetic associations were reported with 4 adverse events following influenza vaccination (narcolepsy, GBS, GCA/PMR, high temperature) and 2 adverse events following measles vaccination (fever, febrile seizure). Conclusion: This scoping review identified numerous genetic associations with vaccine immunogenicity and several genetic associations with vaccine safety. Most associations were only reported in one study. This illustrates both the potential of and need for investment in vaccinomics. Current research in this field is focused on systems and genetic-based studies designed to identify risk signatures for serious vaccine reactions or diminished vaccine immunogenicity. Such research could bolster our ability to develop safer and more effective vaccines.